Las "Cigarrinhas dos canaviais" en Brasil. (IIIa Contribución). Aspectos generales del problema, con especial referencia a Mahanarva posticata en los Estados de Pernambuco y Alagoas - Guagliumi, P. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
After reporting the most important species of Froghoppers which are damaging sugar-cane in the Neotropical region, the author, in this 3rd contribution refers to the (Mhanarva fimbriolata Stal, M. liturata Le P. and Serv., Aeneolamia selecta Wlk., Deois schach F, D. flavopicta Stal, D. incompleta Wlk., D. terrea Germ. and Zulia entreriana Berg), and those with aericolous ones (Mahanarva posticata Stal, M. quadripunctata Wlk., M. (Ipiranga) rubicunda indentata Wlk., M. tristis F. and Tomaspis furcata Germ.). The more important species as sugar-cane pests are M. fimbriolata and M. posticata, their noxiousness lying in the fact that during the adult stage these froghoppers intoxicate sugar-cane leaves, causing serious setbacks in the sugar production. M. fimbriolata is possibly spread throughout the country, attacking sugar-cane and many grasses, and ecologically belongs to what Myers called “savannah froghoppers”; but the second species, M. posticata, only recently was introduced to the Northeastern sugar-cane region in the States of Pernambuco and Alagoas and in this new environment it expanded itself and exploded as a major calamity of the sugar crop. Bionomic data and ecological notes are presented about M. posticata and the discovery of her natural habitat with the primitive host plants, on which it was found also some of the natural enemies; this species can now be included into Myers´ “riparian froghoppers”. About the control of the past in Pernambuco and Alagoas sugar-cane fields, the author points to the initial difficulties encountered in destroying the nymphs and the adults with the use of insecticides, and the not at all satisfactory results obtained with BHC. The actual situation is now much improved, because the pest control is executed with: a) the use of pesticides accordingly with the biological data collected during the last two years; b) the strictly applied cultural systems; and c) the beginning of a Biological Control campaign with the use of one or more natural enemies, discovered in its natural habitat or imported from other countries.